Custos de uma edificação unifamiliar do programa “Minha casa, minha vida”: análise comparativa dos sistemas estruturais de concreto armado e alvenaria estrutural - (:unkn) unknown (Universidade Federal do Pampa, 2017)
It is noted at the same time that the reinforced concrete with conventional masonry fence and the structural masonry with ceramic block are still structural systems widely used in civil construction. In addition, it is possible to perceive that one of the biggest problems faced in Brazil is the housing deficit. In this sense, one possibility of reducing the number of families living in precarious conditions is the investment in popular single-family developments with affordable payment conditions, such as the financing of the Minha Casa, Minha Vida credit program of CAIXA Econômica Federal. In view of the above, it was decided to carry out a budget analysis in which the two structural systems were used for the construction of a same building that fits the criteria of this program. For the preparation of the two budgets TCPO and SINAPI tables were used, in them it is possible to determine the items and sub-items necessary to perform the services and to adopt values to the cost composition. After completing the worksheets, it was determined which structural system was more economical, comparing the final value of housing and the proportion of expenses that the structure generated over the total cost of the work. The results showed that the structural masonry had a final value of 21.41% lower than the reinforced concrete, in which only the structure and the fences had different values, the other budget items had the same value for both Costs, since they do not change independently of the structure adopted. The proportion of spending on the structure in relation to the total housing was 34.74% for reinforced concrete and 29.08% for structural masonry, and for the fences it was 10.24% for the armed concept and 0.91 % for structural masonry.
Keywords: Engenharia civil; Concreto armado; Alvenaria estrutural; Habitação popular; Civil engineering; Reinforced concrete; Structural masonry; Popular housing; CNPQ::ENGENHARIAS